2023
DOI: 10.3389/fped.2023.1083168
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced cavitating Wilms' tumor pulmonary metastasis: Active disease or scarring? A case report and literature review

Abstract: The second most common abdominal tumor in children is Wilms’ tumor, and the lung is where it most often metastasizes. The typical metastases are multiple, peripherally located, round, and variable-sized nodules. Atypical patterns are also possible and may create diagnostic challenges, especially in patients treated with chemotherapy. Among these, cavitating metastases are an anecdotal type of atypical secondary lung lesions. Here, we report a case of a chemotherapy-induced cavitating Wilms' tumor pulmonary met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Interestingly, following our work, several research groups reported that certain chemotherapeutics elicit a de novo prometastatic tumor microenvironment in both preclinical studies and in some patient subpopulations [14][15][16][17][18][19]. Expectedly, the very notion of chemotherapy-induced metastasis was initially disconcerting since chemotherapy is one of the main pillars of cancer treatment, but the aforementioned overwhelming evidence as well as newer clinical case reports [20] have not only led to a concerted search for the causal mechanisms but also to new therapeutic strategies aimed at mitigating chemotherapyinduced metastasis [21][22][23][24][25]. Some of the mechanisms of chemotherapy-induced metastasis reported include increase in extravasation and intravasation [15], increase in intravasation sites called tumor microenvironments of metastasis (TMEM) [16], increased migration and release of circulating tumor cells into the blood stream of cancer patients following chemotherapy [17], increased infiltration of immune cells such as neutrophils [18] and release of prometastatic proteins through extra-cellular vesicles [19].…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, following our work, several research groups reported that certain chemotherapeutics elicit a de novo prometastatic tumor microenvironment in both preclinical studies and in some patient subpopulations [14][15][16][17][18][19]. Expectedly, the very notion of chemotherapy-induced metastasis was initially disconcerting since chemotherapy is one of the main pillars of cancer treatment, but the aforementioned overwhelming evidence as well as newer clinical case reports [20] have not only led to a concerted search for the causal mechanisms but also to new therapeutic strategies aimed at mitigating chemotherapyinduced metastasis [21][22][23][24][25]. Some of the mechanisms of chemotherapy-induced metastasis reported include increase in extravasation and intravasation [15], increase in intravasation sites called tumor microenvironments of metastasis (TMEM) [16], increased migration and release of circulating tumor cells into the blood stream of cancer patients following chemotherapy [17], increased infiltration of immune cells such as neutrophils [18] and release of prometastatic proteins through extra-cellular vesicles [19].…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, following our work, several research groups reported that certain chemotherapeutics elicit a de novo prometastatic tumor microenvironment in both preclinical studies and in some patient subpopulations [ 14 , 15 , 16 , 17 , 18 , 19 ]. Expectedly, the very notion of chemotherapy-induced metastasis was initially disconcerting since chemotherapy is one of the main pillars of cancer treatment, but the aforementioned overwhelming evidence as well as newer clinical case reports [ 20 ] have not only led to a concerted search for the causal mechanisms but also to new therapeutic strategies aimed at mitigating chemotherapy-induced metastasis [ 21 , 22 , 23 , 24 , 25 ]. Some of the mechanisms of chemotherapy-induced metastasis reported include increase in extravasation and intravasation [ 15 ], increase in intravasation sites called tumor microenvironments of metastasis (TMEM) [ 16 ], increased migration and release of circulating tumor cells into the blood stream of cancer patients following chemotherapy [ 17 ], increased infiltration of immune cells such as neutrophils [ 18 ] and release of prometastatic proteins through extra-cellular vesicles [ 19 ].…”
Section: Introductionmentioning
confidence: 99%